Knitted wool stockings in the Museum of London: A study of 16th century construction - Edwards, Lesley O'Connell (Archaeological Textiles Review, 2018)
This paper presents the results of a study of the construction of 13 wool stockings dated to the 16th century, which are held by the Museum of London. Although knitted garments, especially stockings, became very common in later 16th century England, there has been little study of their construction in this period. Each of the stockings was examined in detail, including wale and course counts, leg shaping and heel and toe construction. Other knitted items from the same period in the collection were also examined to compare construction details. The light that these examinations shed on the construction of knitted stockings is discussed in detail, including leg shaping, toe shaping, and an unusual method of heel construction. The paper will also discuss the insights this study provides on knitted stocking construction in this period, including support for archival evidence.